Palatalization and labialization in the Chadic languages of Chad (Afrika und Übersee, 2025)
This paper examines verb data from five Chadic languages of Chad, in order to show the extent to which the prosodies of labialization (LAB) and palatalization (PAL) are relevant to the synchronic analysis of their phonologies. Previous studies have established the synchronic functioning of prosodies in Chadic languages of the Central branch, but not for other branches of the family. Of the languages considered in this paper, one (Heɗe) is from the Masa branch, the other four from the Eastern branch: Somrai, Gabri, and Kabalay from the Chari-Logone subbranch, and Mawa from the Guéra subbranch. In Heɗe and Somrai, the vowel system can be reduced to a single underlying /a/, similar to the analysis claimed for many Central Chadic languages. Epenthetic [ɨ] is added to separate between consonants, and the distinctive prosodic features of LAB and PAL blanket whole words, creating a full set of surface vowels. A consequence of such a system is that high vowels like [ɨ] are marginal, while only the nonhigh vowel /a/ is fully phonemic. Gabri displays these characteristics, but to quite a lesser degree; in this language, pal also seems to play a limited morphological role. The vowel system of Kabalay again shows a dichotomy in behavior between high and nonhigh vowels, but there is only a hint that prosodies are relevant. Mawa clearly shows that the vowel /a/ can be affected by LAB and PAL, but these prosodies do not interact with the seven other phonemic vowels. The article concludes by suggesting that the LAB and PAL prosodies must have functioned in Proto-Chadic, although they have been lost to differing degrees in individual languages in the Chadic languages of Chad.
Keywords: East Chadic; Chad; prosodies; labialization; palatalization